Air Rebusan Seledri Menurunkan Tekanan Darah - Afridah, Wiwik; Setiawan, Budi (Unusa Press, 2013)
The increasing elderly population will lead to problems such as health problems, one of which is hypertension. The purpose of this study was to determine the effect of celery stew on blood pressure in elderly people with hypertension Hulaan Village District Menganti Gresik regency. This study uses a design Case control design with the aging population in the first level of hypertension by 12 people, with a large sample of elderly with hypertension entire first level is 12 people, and how to use the total sampling sampling and divided into 6 groups of 6 cases and the control group with random allocation techniques. Celery stew independent variables and the dependent variable blood pressure. The data was collected by means of measuring the blood pressure recorded recapitulation and analyzed using the Fisher exact test with α = 0.05. The research results obtained from 6 groups of cases that were given celery stew all experienced a decrease in blood pressure, whereas in the control group of 6 people who were not given celery stew is only 1 person that declined. Fisher Exact test results obtained ρ (0.015) <α (0.05), means that the research hypothesis is accepted ie no celery stew effect on blood pressure in elderly people with hypertension Hulaan Village District Menganti Gresik Regency. The conclusions of this study are no celery stew effect on blood pressure of elderly with hypertension. Hypertensive patients are expected to maintain your diet, multiply to consume fruits and vegetables that contain potassium, as well as a healthy lifestyle change.